2011
DOI: 10.1007/s10439-011-0354-x
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Real-Time PCR Approach for the Detection and Characterization of Endothelial Cells in Whole Blood

Abstract: Pathological inflammation and endothelial dysfunction in atherosclerosis causes endothelial cell detachment from affected vasculature giving rise to circulating endothelial cells (CECs). A blood-based assay that can detect and characterize CECs in atherosclerosis could serve as a valuable diagnostic. Thus, we sought to develop a prototypic assay that detects and characterizes the inflammatory state of endothelial cells present in blood. For this purpose, we spiked resting and inflamed human umbilical vein endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Thus, as a first step in the present study, we compared, at a range of concentrations, the effect of 1a to that of MMI in terms of the ability to inhibit TNF-α-induced VCAM-1 expression. We have previously shown that TNF-α induces VCAM-1 mRNA and protein expression in HUVEC (Dagia and Goetz, 2003; Deosarkar et al, 2011). We chose to initially focus this study on TNF-α induced VCAM-1 protein expression (as opposed to VCAM-1 mRNA expression) since VCAM-1 protein expression is more functionally relevant than VCAM-1 mRNA.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, as a first step in the present study, we compared, at a range of concentrations, the effect of 1a to that of MMI in terms of the ability to inhibit TNF-α-induced VCAM-1 expression. We have previously shown that TNF-α induces VCAM-1 mRNA and protein expression in HUVEC (Dagia and Goetz, 2003; Deosarkar et al, 2011). We chose to initially focus this study on TNF-α induced VCAM-1 protein expression (as opposed to VCAM-1 mRNA expression) since VCAM-1 protein expression is more functionally relevant than VCAM-1 mRNA.…”
Section: Resultsmentioning
confidence: 97%
“…The reported number of CEC in human clinical trials varies greatly and depends on the applied detection method and exclusion parameters . The application of antibody‐coated metal beads used for microscopic evaluation was first applied for the quantification of CEC .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rapid discovery of monoclonal anti‐porcine antibodies should be monitored to facilitate further enhancement of the CEC detection protocol. Suitable markers include endothelial markers such as CD31 (PECAM‐1), CD34 (hematopoietic progenitor cells), CD45 (pan‐lymphocytic), CD133 (hematopoietic stem cells), CD144 (VE‐Cadherin), CD146, and, more recently, mRNA levels have been used in humans . Unfortunately, CD105 and CD146 are also both expressed on a subset of human lymphocytes and vascular pericytes .…”
Section: Discussionmentioning
confidence: 99%
“…Their study, in particular gene expression study, is therefore very important for the understanding of the physiopathology of endothelial diseases. As an example, recently an RNA assay was shown able to detect inflamed endothelial cells circulating in whole blood of atherosclerosis patients thus providing proof-of-concept for the diagnosis of pathological inflammation and endothelial dysfunction in atherosclerosis [9]. Nowadays, the most common approach for HUVEC isolation with a good yield from the human umbilical vein is the enzymatic removal by e.g.…”
Section: Introductionmentioning
confidence: 99%